Evaluating Educational Inputs in Undergraduate Education - Dolan, Robert C.; Jung, Clarence R.; Schmidt, Robert M. (The Review of Economics and Statistics, 1985)
This study examines institutional production of higher education. An interesting aspect of this production process is that two of the more important inputs, students and faculty, enter upon considerable self-selection. To address this interdependence, the production relationship is specified by a three-equation simultaneous model in which the quality of college output, faculty, and students are treated endogenously. The significance of simultaneity is demonstrated in an empirical model estimated via three-stage least-squares for a sample of 174 private undergraduate institutions. The results offer clear implications regarding the allocation of institutional resources across the basic factors in educational production. This paper examines the input-output relationship for private undergraduate education. The study falls generally within the economic literature that has analyzed the educational process via a production function specification (Astin, 1968; Bowles, 1970; Summers and Wolfe, 1977; Hanushek, 1979; McGuckin and Winkler, 1979). However, we extend the argument that research assessments of the educational process are not dealing with a production function in the classic sense. For example, the purchaser of the product-the student-is also one of the more important inputs. Further, the non-profit orientation of most universities reduces incentives for cost minimization.' The implication is that the educational process is far more complicated than a simple, production-functional rendering indicates. To demonstrate this point, we estimate a three-equation simultaneous model in which the quality of students, faculty, and college output are treated endogenously.2 This study's broad objective is to identify more clearly the relative contribution of the many human and nonhuman resources combining to produce quality under-